Demystifying academic writing : genres, moves, skills, and strategies - Fang, Zhihui (Routledge, 2021)
"Accessible and informative, this book is designed to enhance the capacity of graduate and undergraduate students, as well as early career scholars, to write for academic purposes. Fang describes the key genres and types of academic writing, explains common rhetorical moves, offers linguistic strategies and insights to give students the skills they need for effective academic writing across genres and disciplines. Fang's functional linguistic approach to academic writing enables readers to do so much more than write well-formed grammatical sentences; it leverages writing as a meaning-making process to position language choices as the central focus. Covering reading responses, book reviews, essays, empirical research articles, grant proposals, and more, this text is an all-in-one resource for building a successful career in academic writing and scholarly publishing. Each chapter features authentic writing examples as well as thoughtful analysis, and practical applications, and reflective questions. Fang compliments these examples with self-assessment tools for writers. Assuming no technical knowledge, this text is ideal for both non-native and native English speakers alike, and for courses in academic writing, composition, and L2 writing instruction"- Resumé vydavatele